Who Pays, Who Rules? A Comparative Constitutional Inquiry into Party Finance Regulation in Indonesia, the Philippines, and Thailand. - Moch Andry Wikra Wardhana Mamonto; Mohammad Arif; Fitriani Ahlan Sjarif (Constitutionale, 2025)
This study examines the regulatory deficiencies in Indonesia’s political finance system, particularly the absence of laws governing party income sources. Although existing rules address campaign spending and financial reporting, they lack limits on donations and fail to restrict high-risk, foreign-linked, or opaque contributions. Using a normative legal method supported by comparative, statutory, and conceptual analysis, the research draws on experiences from Thailand and the Philippines to identify best practices for reform. It argues that source-based regulation is essential to uphold constitutional equality and electoral integrity. The proposed reform agenda rests on three pillars: introducing statutory ceilings on donations, prohibiting high-risk and anonymous contributions, and institutionalising public financing tied to democratic performance. The findings show that Indonesia’s weak regulatory framework fosters elite capture, erodes internal party democracy, and diminishes public trust. By integrating these reforms, Indonesia can close legal gaps, strengthen constitutional democracy, and contribute to global discourse on political finance reform.